2012
DOI: 10.5614/itbj.eng.sci.2012.44.3.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ozonation Process on Bromide-Containing Groundwaters in Bandung Area and Its Surroundings

Abstract: Disinfection process was applied as the last step of the water treatment to kill pathogenic bacteria in the water. However, according to several studies, the ozonation disinfection process could form undesired by-products. One of the by-products potentially affecting human life is bromate produced from bromide ionic-containing water. This study was carried out to examine the effect of raw water characteristics and pH on bromate formation. Also, the performance of bromate formation for a period of exposure time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, the change of spectral slopes during ozonation indicated the variation in molecular weight, DOM, and inorganic characteristics. [28] The ozonation process can increase the bromate formation in bromidecontaining water, [27,61] which influences the brominated disinfection by-products (B-DBPs) formation potential. [10,27] Similarly, an increase in spectral slopes correlates with the ratio of BrO 3 /Br − in water during the ozonation process.…”
Section: Correlation Between Dom Fractions and Spectral Slopesmentioning
confidence: 99%
“…Furthermore, the change of spectral slopes during ozonation indicated the variation in molecular weight, DOM, and inorganic characteristics. [28] The ozonation process can increase the bromate formation in bromidecontaining water, [27,61] which influences the brominated disinfection by-products (B-DBPs) formation potential. [10,27] Similarly, an increase in spectral slopes correlates with the ratio of BrO 3 /Br − in water during the ozonation process.…”
Section: Correlation Between Dom Fractions and Spectral Slopesmentioning
confidence: 99%
“…Previous research [13] has reported that the presence of THM in African raw water could reach 3-18 μg/L depending on the season. The presence of chlorinated HAA5 in river water has been reported to reach 41.2-308 μg/L in Portugal, with the presence of total organic carbon (TOC) and bromide ion at 6 and 0.7 mg/L, respectively [14]. The presence of HAAs and bromide ions has been reported to be below the detection limit in water from the Quebec River [15].…”
Section: Introductionmentioning
confidence: 99%